Warning of damage to health services safe background or Law 29,414? - Véliz Márquez, José (2010)
Faced with increased demands for medical malpractice, there is the problem of identifying a strategy that addresses immedíate damage caused by errors or adverse events loc for healthcare practice. The report identifies 3 thesis, two already known: to establish insurance funds, and one that is based on the simple use of the budget allocated to health facilities, as indeed is often done, in many cases, though unofficially. The assessment of what happened in our reality, and an evaluation of the ethical, are used to determine the best strategy would be to use the budget as the other two more expensive health processes for administrative payments to the intermedíary in the case of insurance, or investment resources, in the case of funds and having to use the same time health workers to the respective health services. Rising prices aggravated the situation for patients in poor or extremely poor. Another disadvantage, the most serious, according to the author, is the distortion of the doctorpatient relationship, as the atmosphere of controversy set next to the anger, fear and possibility or getting money to litigate, placed on either side of the trench to patient and physician, creating mistrust. We conclude that the mere use of the budget, possibly with the regulation of Law 29414, avoids higher costs and keeps the physician-patient relationship in a climate of confidence which gives the mutual task of curing or at least improve patient health.